Enhanced Landfill Leachate Treatment using Spiral Symmetry Stream Anaerobic Bioreactor and Sequential Batch Reactor - Mwizerwa, Innocent Tayari; Chen, Xiaoguang; Hu, Baolan; Muhammed, Ismail (Journal of Environmental Accounting and Management, 2026)
Landfill leachate has become a disaster in recent years because of high strength liquid compounds. We conducted biological treatment enhanced by chemical precipitation for COD and NH$_{4}$-N removal through SSSAB and SBR in series. COD and NH$_{4}$-N were determined before and after treatment in both SSSAB and SBR reactor for aerobic- anaerobic treatment prior to chemical precipitaion. We found out that SSSAB reported better NH$_{4}$-N removal rates of 97.7% with reduced COD removal rate at 7.7 % in five samples. On the other hand, compared with 98% COD removal rates and 96.1% for SBR. SBR and SSSAB were efficient in removing NH$_{4}$-N than COD. Chemical precipitation showed a novel impact on biological treatment. The quiet removal rates are related to the little aeration time to facilitate the completion of the nitrification process. Struvite precipitation contributed to a change in the Chemical oxygen demand and Ammonium nitrogen removal through the formation of calcium phosphate and reducing the inhibition of biological treatment in SSSAB. We report the first treatment efficiency route for high strength landfill leachate for COD and NH$_{4}$-N removal.